Cytokine gene polymorphism [tumor necrosis factor-alpha (–308), IL-10 (–1082), IL-6 (–174), IL-17F, 1RaVNTR] in pediatric patients with primary immune thrombocytopenia and response to different treatment modalities. Issue 3 (April 2016) - Mokhtar, Galila M.; El-beblawy, Nagham M.S.; Adly, Amira A.; Elbarbary, Nancy S.; Kamal, Tarek M.; Hasan, Esraa M.
Abstract : To evaluate the association between development, progression, and response to therapy among patients with immune thrombocytopenia (ITP) and different cytokine gene polymorphisms known to be related to autoimmunity [tumor necrosis factor (TNF)-alpha, interleukin (IL)-10, IL-6, IL-17, IL-1Ra]. A total of 50 pediatric patients with ITP (20 newly diagnosed, 30 chronic) and 50 healthy controls were investigated via PCR-restriction fragment length polymorphism analysis for cytokine gene polymorphism. Compared with controls, all patients showed a higher frequency of IL-6−174 CC [ P = 0.0001, odds ratio (OR) = 7.048, 95% confidence interval (CI) = 2.18–22.7], higher GA genotype of TNF-α (−308) ( P = 0.001, OR = 6.469, 95% CI = 2.0–20.9), higher CC genotype of IL-17F ( P = 0.0001, OR = 55.545, 95% CI = 14.4–213.2), higher GG of IL-10−1082 ( P = 0.029, OR = 3.6, 95% CI = 1.08–12.18), and A1A2 genotype of IL-1Ra VNTR ( P = 0.039, OR = 2.374, 95% CI = 1.03–5.4). IL-10 GA and IL-1Ra A1A1 genotypes were higher among chronic patients ( P = 0.042, P = 0.001 respectively) compared with newly diagnosed ones. Best platelet response to steroid treatment was found among GC genotype of IL-6 (–174) and GG genotype of IL-10 (–1082) in all patients with ITP. This suggests that previously mentioned cytokine gene polymorphisms possibly contribute to the susceptibility of acquisition of childhood ITP. Furthermore, GA genotype of IL-10 and A1A1 genotype of IL-1Ra polymorphisms are associated with increased risk of chronic ITP. IL-6 (–174) and IL-10 (–1082) genes might play a role in the effectiveness of steroid therapy among patients with ITP.